A case study: using integrated care pathways in mental health care - Hall, Julie (2010)
Background: Integrated Care Pathways (ICPs) are prearranged processes of care which are being increasingly used to deliver mental health services. The literature reveals difficulties in their development and implementation, and a lack of empirical evidence to support their use.